2018
DOI: 10.1021/acs.nanolett.8b02991
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assembly of Diverse Bacterial Microcompartment Shell Architectures

Abstract: Bacterial Microcompartments (BMCs) are organelles composed of a selectively permeable protein shell that encapsulates enzymes involved in CO2 fixation (carboxysomes) or carbon catabolism (metabolosomes). Confinement of sequential reactions by the BMC shell presumably increases the efficiency of the pathway by reducing the crosstalk of metabolites, release of toxic intermediates, and accumulation of inhibitory products. Because BMCs are composed entirely of protein and self-assemble, they are an emerging platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 48 publications
4
105
0
Order By: Relevance
“…CcmM in the β-carboxysome appears as two isoforms, a 35-kDa truncated CcmM35 and a full-length 58-kDa CcmM58 (Long et al, 2007;Long et al, 2010;Long et al, 2011). CcmM35 contains three Rubisco small subunit-like (SSU) domains that interact with Rubisco (Hagen et al, 2018b;Wang et al, 2019), whereas CcmM58 has an N-terminal γ-CA-like domain in addition to the SSU domains and recruits CcaA to the shell. RbcX is recognized as a chaperonin-like protein for Rubisco assembly (Emlyn-Jones et al, 2006;Saschenbrecker et al, 2007;Occhialini et al, 2016); it has been recently revealed to serve as one component of the carboxysome and play roles in mediating carboxysome assembly and subcellular distribution (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CcmM in the β-carboxysome appears as two isoforms, a 35-kDa truncated CcmM35 and a full-length 58-kDa CcmM58 (Long et al, 2007;Long et al, 2010;Long et al, 2011). CcmM35 contains three Rubisco small subunit-like (SSU) domains that interact with Rubisco (Hagen et al, 2018b;Wang et al, 2019), whereas CcmM58 has an N-terminal γ-CA-like domain in addition to the SSU domains and recruits CcaA to the shell. RbcX is recognized as a chaperonin-like protein for Rubisco assembly (Emlyn-Jones et al, 2006;Saschenbrecker et al, 2007;Occhialini et al, 2016); it has been recently revealed to serve as one component of the carboxysome and play roles in mediating carboxysome assembly and subcellular distribution (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the formation of hexamers combining CsoS1 and CcmK subunits should not be excluded. Indeed, considering that the YFP domain attached to CsoS1 monomers is considerably bulkier than SUMO domains exploited by the same authors to prevent BMC-H component assembly in vitro [45], the resulting CsoS1-YFP hexamers would be expected to be assembly-incompetent. If these arguments hold true, fluorescence puncta observed in vivo should result from the integration on shells of CsoS1-YFP/CcmK hexamers.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined if shell-cytochrome H 5 retained the capability to form the reported compartment assemblies when combined with wildtype Haliangium ochraceum (HO) BMC shell proteins (Sutter et al, 2017). We performed a recently-described in vitro BMC assembly (Hagen A. R. et al, 2018), where three HO shell proteins (BMC-H, BMC-P [pentamer], and BMC-T [trimer]) are used to assemble a spherical, hollow protein compartment (Sutter et al, 2017). When H 5 shell-cytochrome was substituted for native BMC-H in these assemblies, we found it associated with native BMC-P and BMC-T proteins, although the strength of the association was greatly enhanced by including wild-type BMC-H in the reactions (Supplementary Figure 8A).…”
Section: Higher-order Structure Assembly Of Shell-cytochromesmentioning
confidence: 99%
“…When H 5 shell-cytochrome was substituted for native BMC-H in these assemblies, we found it associated with native BMC-P and BMC-T proteins, although the strength of the association was greatly enhanced by including wild-type BMC-H in the reactions (Supplementary Figure 8A). Assembly reactions containing only H 5 with native BMC-P and BMC-T, contained higher-order structures resembling the size and shape of HO compartments (Figure 4D), although these structures appeared less robust than the published compartments using WT BMC-H proteins (Sutter et al, 2017;Hagen A. R. et al, 2018;Ferlez et al, 2019). Indeed, H 5 -based assemblies frequently appeared as compartments with "broken shells" or as clusters of partially-assembled shell fragments (Supplementary Figure 8B).…”
Section: Higher-order Structure Assembly Of Shell-cytochromesmentioning
confidence: 99%